Field visit in Punjab, India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Last year our South Asia office went for a field visit to learn more about current farming activities, and here are some of the pictures from that visit, showing farmers working hard in the field. Photo : Nirmal Sigtia (CCAFS SA).